Model of the Increase of Accurate Computer Learning Achievement on Islamic Banking and Accounting Students Program - Mutiatul Khasanah, S; Yanto, H (KnE Social Sciences, 2018)
The result of preliminary study in SMK N 1 Kudus, indicates that there is 35,26% of twelfth graders of Islamic Banking and Accounting students who have not completed final exam of the semester. In addition, the results of the students final exam of the semester decreased by 16,67 % when compared with the results of midterms. The purpose of this study is to determine the effect of computer anxiety, computer knowledge, computer attitude, and self efficacy in improving Accurate computer learning achievement. This study is a quantitative study. The population and sample of the study are 156 twelfth graders of Islamic Banking and Accounting students program SMK N 1 Kudus. The methods used to collect data were documentation and questionnare. Data in this research is analyzed using descriptive statistics, correlation analysis, and path analysis with AMOS 22. The result showed that computer knowledge and self efficacy have no effect on computer Accurate learning achievement. Computer anxiety has negative effect on self efficacy 34,6%. While the computer attitude has positive effect on self efficacy 30,1%. However, computer knowledge has no effect on self efficacy. Computer anxiety has negative effect on computer knowledge 32,6% and computer attitude 30,2%. Based on the results of the study it can be concluded that self efficacy is influenced by computer anxiety and computer attitude. Computer anxiety have negatif effect on computer knowledge and computer attitude. Suggestion given in this research is the students can increase computer anticipation in order to reduce the level of computer anxiety by improving practice both at school and training institute. Keywords: Computer Anxiety, Computer Knowledge, Attitude Computer, Self Efficacy, Accurate Computer Learning Achievement.